Spaces for learning and implementation of technological resources in vocational training - Fabregat-Pitarch, Antonio; Gallardo-Fernández, Isabel María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Given the diversity and complexity that we live in the classroom, interesting tasks are proposed that involve students in the importance of daily work and personal commitment to learn the contents of the subject. This text is born within the framework of a broader Project that investigates the analisis of classroom situations in Vocational Training (VT) from a qualitative research approach. This experience is linked to the sociocultural theory of teaching and, following Freire´s approach, takes as a reference the reflection and action of people on the Word to transform it.